Immuno‐pharmacological characterization of group II metabotropic glutamate receptors controlling glutamate exocytosis in mouse cortex and spinal cord. (29th October 2017) - Olivero, Guendalina; Bonfiglio, Tommaso; Vergassola, Matteo; Usai, Cesare; Riozzi, Barbara; Battaglia, Giuseppe; Nicoletti, Ferdinando; Pittaluga, Anna
Abstract : Background and Purpose: We recently proposed the existence of mGlu3 ‐preferring autoreceptors in spinal cord terminals and of mGlu2 ‐preferring autoreceptors in cortical terminals. This study aims to verify our previous conclusions and to extend their pharmacological characterization. Experimental Approach: We studied the effect of LY566332, an mGlu2 receptor positive allosteric modulator (PAM), and of LY2389575, a selective mGlu3 receptor negative allosteric (NAM) modulator, on the mGlu2/3 agonist LY379268‐mediated inhibition of glutamate exocytosis [measured as KCl‐evoked release of preloaded [ 3 H]‐D‐aspartate]. The mGlu2 PAM BINA and the mGlu3 NAM ML337, as well as selective antibodies recognizing the N‐terminal of the receptor proteins, were used to confirm the pharmacological characterization of the native receptors. Key Results: Cortical synaptosomes possess LY566332‐sensitive autoreceptors that are slightly, although significantly, susceptible to LY2389575. In contrast, LY566332‐insensitive and LY2389575‐sensitive autoreceptors are present in spinal cord terminals. BINA and ML337 mimicked LY566332 and LY2389575, respectively, in controlling LY379268‐mediated inhibition of glutamate exocytosis from both cortical and spinal cord synaptosomes. Incubation of cortical synaptosomes with anti‐mGlu2 antibody prevented the LY379268‐induced inhibition of glutamate exocytosis, and this response was partially reduced by the anti‐mGlu3 antibody. Incubation of spinal cord synaptosomes with the anti‐mGlu3 antibody abolished LY379268‐mediated reduction of glutamate exocytosis from these terminals, while the anti‐mGlu2 antibody was inactive. Western blot analysis and confocal microscopy data were largely consistent with these functional observations. Conclusions and Implications: We confirmed that mGlu3 ‐preferring autoreceptors exist in spinal cord terminals. Differently, cortical glutamatergic terminals possess mGlu2 /mGlu3 heterodimers, whose inhibitory effect is largely mediated by mGlu2 receptors.